Assessing the Efficacy of Ventilation of Anesthetized Neonatal Calves Using a Laryngeal Mask Airway or Mask Resuscitator - Armstrong, Laura; Caulkett, Nigel; Boysen, Søren; Pearson, Jennifer M.; Knight, Cameron G.; Windeyer, M. Claire (Frontiers in Veterinary Science, 2018)
Calves that have undergone a dystocia are often hypoxic and acidemic, which can result in reduced vigour and subsequent mortality. Methods of field resuscitation of apneic newborn calves are often ineffective and therefore underutilized. This proof-of-concept study aimed to determine the efficacy of the laryngeal mask airway (LMA) as well as the current industry standard method of ventilation, the McCulloch Calf Aspirator/ Resuscitator (MMR) for positive pressure ventilation of neonatal calves. Five LMA models of various sizes were first tested in cadaver heads to assess anatomical fit. Three LMA models in two sizes each were then tested in two anesthetized calves to determine the model best suited to ventilate calves. Next, the selected LMA and the MMR were both assessed for efficacy of ventilation. Six anesthetized calves had hypoventilation induced by administering alfaxalone intravenously. Calves were ventilated for 3 minutes with the LMA, allowed a brief washout period, then given a second administration of alfaxalone prior to ventilation with the MMR. Serial arterial blood gas analyses were performed prior to ventilation (baseline), at 1, 2, and 3 minutes during ventilation, and 1 minute after ventilation had ceased. Success of ventilation was assessed by monitoring partial pressure of oxygen (PaO2), partial pressure of carbon dioxide (PaCO2), bicarbonate (HCO3-), pH, L-lactate, and hemoglobin saturation (SaO2) in arterial blood. One-way analysis of variance was used to assess the efficacy of ventilation of each device compared to baseline. For the LMA, PaO2, SaO2, and pH were significantly higher than baseline throughout ventilation and PaCO2 was significantly lower than baseline at 1 minute of ventilation. For the MMR, PaO2 and SaO2 were significantly higher and PaCO2 and HCO3- were significantly lower than baseline for 1 to 2 minutes of ventilation. This proof-of-concept study showed the LMA is an effective means of ventilating neonatal calves, as was the MMR.